Peran Pemoderasi Corporate Business Risk Terhadap Hubungan CSR Disclosure, Integrated Reporting, Dan Corporate Reputation - Hakki, Tandry Whittleliang; Andriani, Cinthia; Natalia, Michelle (Politeknik Ganesha Medan, 2024)
Many companies with capabilities in the midst of an uncertain economy due to the Covid-19 pandemic that is currently sweeping the world and especially in Indonesia have also had an impact, these companies are trying to maintain their business activities. In connection with the ero-carbon issue proclaimed by the G20 countries, many private companies are now developing what is called Corporate Social Responsibility (CSR). This study aims to analyze (1) the effect of CSR disclosure on corporate reputation (2) the effect of integrated reporting on corporate reputation. (3) The role of Corporate Business Risk as a moderator of the Effect of CSR Disclosure on Corporate Reputation. (4) The role of Corporate Business Risk as a moderator of the Impact of Integrated Reports on Corporate Reputation. By using purposive sampling with the criteria of banking sector companies listed on the Indonesia Stock Exchange in a row for the 2016-2020 period, Companies that consistently publish annual reports during the 2016-2021, Companies that have been audited by a Public Accounting Firm in the 2016-2020. The results of the research show that the Integrated Report has an effect on Corporate Reputation but CSR Disclosure has no effect on Corporate reputation. Then Corporate Business Risk moderates the effect of Integrated Report on Corporate Reputation but does not moderate the effect of CSR Disclosure on Corporate Reputation